Charactered Teachers’ Personality Competencies within Social Interactions - Hirlan Maulana; Solihin Nurhayat Kholbi; Dendi Muhamad Syafei; Lina Herlina (Nusa Putra University, 2021)
This study aims to provide views related to the formation of professional teacher competencies through interaction on the current realities. The method used in this research was qualitative descriptive method. Data was collected directly through interviews which were then analyzed through literature review with theories that have occurred among the teaching profession. The results of this study are expected to be able to describe how to form teachers’ personality in accordance with the character competence of the teachers. The output that can be generated is that teachers can implement himself as a teacher who has a high work ethic, has noble character and of course has a character in accordance with the essence of a teacher himself. The importance of a teacher to be able to interact socially in order to be able to solve problems that occur in the community so that the results of learning in students can be realized in everyday life.